OBSERVATIONS OF EARTH TIDES AND EARTH'S FREE OSCILLATIONS BY A SUPERCONDUCTING GRAVIMETER AT SYOWA STATION ANTARCTICA - サトウ, タダヒロ; シブヤ, カズオ; カミヌマ, カツタダ; オオエ, マサツグ; タムラ, ヨシアキ; フクダ, ヨウイチ; カナオ, マサキ; SATO, Tadahiro; SHIBUYA, Kazuo; KAMINUMA, Katsutada; OOE, Masatsugu; TAMURA, Yoshiaki; et al. (National Institute of Polar Research, 1995)
P(論文) As part of the five-year earth science program (1993-1998) in the Japanese Antarctic Research Expedition, observations of earth tides and earth's free oscillations are being carried out at Syowa Station by a superconducting gravimeter, SCG, (T. SATO et al.; Proc. NIPR Symp. Antarct. Geosci., 6,17,1993). The continuous observations by the SCG started on March 22,1993. We examined the performances of this observation in the frequency bands of the earth tide or longer. The data obtained for eleven months from March 1993 to January 1994 have been used in the present analysis. (1) Data processing : Original 2-s data of the tide channel were sampled every 1 min through a digital filter to reduce high frequency noises, then these data were resampled every 1 hour for the tidal analysis. Sensitivity (scale factor) of the gravimeter was tentatively given by comparing the amplitude of M2 constituent of the SCG record with that previously obtained from the observation by a LaCoste & Romberg gravimeter (M. KANAO and T. SATO; Proc. 12th Int. Symp. on the Earth Tides held at Begin, in press). (2) Short period tide : The short period tides whose periods are shorter than one week were analyzed by means of a FORTRAN program called as BAYTAP-G (Y. TAMURA et al.; Geophys. J. Int., 104,507,1991). The response of the gravity data to the atmospheric pressure changes was simultaneously calculated with that to the tide generating forces. The analysis shows that the tidal parameters, i.e. amplitude factors and phase lags, obtained by the SCG are consistent with the previous values given by M. KANAO and T. SATO (Proc. 12th Symp. on the Earth Tides, 1993,in press). Thus we recognize that the amplitude factors, especially of the semidiurnal tides at Syowa Station are large enough to exceeding the observation errors. The reasons for this should be explained first. (3) Long period tide : The long period tides were analyzed using the drift component obtained from the analysis of short period tides. This analysis shows that the SCG ...